Photoreceptor Mediated Plant Growth Responses: Implications for Photoreceptor Engineering toward Improved Performance in Crops - Mawphlang, Ophilia I. L.; Kharshiing, Eros V. (Frontiers in Plant Science, 2017)
Rising temperatures during growing seasons coupled with altered precipitation rates presents a challenging task of improving crop productivity for overcoming such altered weather patterns and cater to a growing population. Light is a critical environmental factor that exerts a powerful influence on plant growth and development ranging from seed germination to flowering and fruiting. Higher plants utilise a suite of complex photoreceptor proteins to perceive surrounding red/far-red (phytochromes), blue/UV-A (cryptochromes, phototropins, ZTL/FKF1/LKP2) and UV-B light (UVR8). While genomic studies have also shown that light induces extensive reprogramming of gene expression patterns in plants, molecular genetic studies have shown that manipulation of one or more photoreceptors can result in modification of agronomically beneficial traits. Such information can assist researchers to engineer phototreceptors via genome editing technologies to alter expression or even sensitivity thresholds of native photoreceptors for targeting aspects of plant growth that can confer superior agronomic value to the engineered crops. Here we summarise the agronomically important plant growth processes influenced by photoreceptors in crop species, alongwith the functional interactions between different photoreceptors and phytohormones in regulating these responses. We also discuss the potential utility of synthetic biology approaches in photobiology for improving agronomically beneficial traits of crop plants by engineering designer photoreceptors.